Awareness regarding hepatitis B and it’s vaccination status among medical students, doctors and paramedics studying & working at DHQ Teaching Hospital, Sahiwal - Diwan, Rana Aamir; Ahmad, Khalil; Hashmi, Fahad Mukhtar; Arslan, Muhammad; Bhatti, Muhammad Nabeel (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACT Introduction: Hepatitis B is a risk factor for Health Care Workers (HCW) and medical students attending wards at hospital. Hepatitis B vaccine has been recommended since 1982 for use by HCWs to prevent HBV infection. The aim of this study was to evaluate the vaccination coverage among HCWs and medical students, their level of knowledge regarding vaccination as well as and their beliefs regarding Hepatitis B vaccine at a Teaching District Headquarter (DHQ) Hospital of Punjab, Pakistan. Subjects and Methods: This cross sectional descriptive study based on a questionnaire-based survey was carried out at DHQ Teaching Hospital, Sahiwal, Pakistan from 01-04-2019 to 31-07-2019. Doctors, medical students and paramedical staff involved in active physical care of the patients were included in the study. Results: A total of 300 participants were provided questionnaire including consent, out of which 285 participants responded. There were 127 doctors (44.56%), 86 medical students (30.18%) and 72 paramedics (25.26%). 132 (46.31%) participants were fully vaccinated, 9.12% had received 2 doses of vaccine, 8.77% received only one dose whereas 35.43% were unvaccinated. Out of unvaccinated individuals, 32.35% reasoned lack of time being the main cause followed by other reasons including lack of need, lack of awareness and accessibility. Conclusion: This study showed that vaccination coverage among HCWs was alarmingly low along with lesser knowledge of vaccination and infection. Therefore, HCWs and medical students are at an increased risk of acquiring Hepatitis B infection.